2012
DOI: 10.1105/tpc.112.096909
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Role of the N-Terminal Domain of the Orange Carotenoid Protein in Cyanobacterial Photoprotection: Importance of a Positive Charge for Phycobilisome Binding

Abstract: Most cyanobacteria, under high light conditions, decrease the amount of energy arriving at the reaction centers by increasing thermal energy dissipation at the level of the phycobilisome, the extramembranous antenna. This mechanism is induced by photoactivation of the Orange Carotenoid Protein (OCP). To identify how the activated OCP interacts with phycobilisomes (PBs), several OCP mutants were constructed, and the influence of mutations on photoactivity, stability, and binding to PBs was characterized. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 27 publications
7
99
1
Order By: Relevance
“…4B). Recently, the OCP has been proposed to interact with the phycobilisome through its N-terminal domain, specifically through the surface surrounding Arg155, which is typically buried in interaction with the C-terminal domain in the OCP o (18). We have confirmed the interaction of the FRP with the C-terminal domain of the OCP by coimmunoprecipitation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…4B). Recently, the OCP has been proposed to interact with the phycobilisome through its N-terminal domain, specifically through the surface surrounding Arg155, which is typically buried in interaction with the C-terminal domain in the OCP o (18). We have confirmed the interaction of the FRP with the C-terminal domain of the OCP by coimmunoprecipitation.…”
Section: Discussionsupporting
confidence: 68%
“…In the strains overexpressing the C-terminal domain, the original WT OCP was suppressed by partial deletion of the slr1963 gene as described in ref. 18. The His-tagged C-terminal domain was isolated by Nickel affinity as described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…S1, and Table S6). R155, which participates in a salt bridge between the NTD and CTD, and which plays an important role in interaction with the phycobilisome during energy dissipation (12), is associated with water cluster 1, which includes HOH1020 (Fig. 4 and Fig.…”
Section: Hdx-msmentioning
confidence: 99%
“…A recent study of the OCP bound to the carotenoid canthaxanthin (OCP-CAN) showed that photoactivation of the OCP results in a substantial translocation (12 Å) of the carotenoid deeper into the NTD (9). Mutational analyses of the full-length OCP and biochemical studies on the constitutively active NTD [commonly known as the red carotenoid protein (RCP)] suggested that the NTD and CTD at least partially separate, resulting in the breakage of an interdomain salt-bridge (R155-E244) upon photoactivation (9)(10)(11)(12). Together, the previous studies suggest that large-scale protein structural changes in the OCP accompany carotenoid translocation upon light activation; however, such changes in the context of the full-length protein have yet to be experimentally demonstrated.…”
mentioning
confidence: 99%
“…The two domains are joined by a long (;25 amino acids) and flexible loop linker (Kerfeld et al, 2003;Wilson et al, 2010). OCP o has a closed conformation, and OCP r has an open conformation, allowing the interaction between the carotenoid and the bilin in the core of phycobilisome (Wilson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%